Beyond the hype: re-evaluating efficacy metrics and modeling rigor for MSC-EVs-based therapy in acute brain injury - Zhou, Fating; Wang, Hongxia; Zhu, Xiaodan; Huang, Rui; Jiang, Xuemei; Duan, Haizhen; Ma, Yu; Ai, Shanmu (Frontiers in Medicine, 2025)
Acute brain injuries (ABI), such as traumatic brain injury, stroke, hypoxia-induced brain injury, and cardiac arrest, are critical and life-threatening conditions that contribute to substantial mortality and long-term disability. Despite extensive translational efforts, no effective therapy has improved long-term functional outcomes, highlighting a critical unmet need. Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) have emerged as promising cell-free therapeutic platform, offering multifaceted repair capabilities. This review synthesizes current evidence supporting the neuroprotective effects of MSC-EVs, which operate through synchronized immunomodulation, anti-apoptotic signaling, enhancement of neurogenesis, and stimulation of angiogenesis. We further delineated the fundamental EVs biology, including biogenesis pathways, spatiotemporal biodistribution, and blood–brain barrier (BBB) trafficking mechanisms that underpin therapeutic efficacy. Collectively, we established MSC-EV cargo as a strategic solution to unmet neuroprotective needs while mapping clinical translation roadmaps to accelerate the rational development of regenerative neurotherapeutics.